Friction losses in valves and fittings for viscoplastic fluids - Telis-Romero, J.; Polizelli, M. A.; Gabas, A. L.; Telis, VRN (Canadian Soc Chemical Engineering, 2005)
Data on pressure drop were obtained in stainless steel, sanitary fittings and valves during laminar and turbulent flow of aqueous suspensions of sucrose and bentonite. The rheological properties of these suspensions were determined and the Bingham model provided the best fitting with the experimental data. Friction losses were measured in fully- and partially-open butterfly and plug valves, bends and union. Values of loss coefficients (k(f)) were calculated and correlated as functions of the classical Reynolds number and the Reynolds number proposed by Govier and Aziz (1972) for viscoplastic fluids. The two-k method and a new proposed model presented the best adjustments for the Govier and Aziz Reynolds number, and Hedstrom and classical Reynolds numbers, respectively.
Keywords: pressure drop; non-Newtonian fluids; friction factors; loss coefficients